Time Series Prediction of Rainfall and Temperature Trend using ARIMA Model - Masum, M. H.; Islam, R.; Hossen, M. A.; Akhie, A. A. (Journal of Scientific Research, 2022)
Rainfall and temperature are two key factors to examine while assessing climate change. Bangladesh has witnessed extremes in rainfall and temperature during the previous few decades, affecting both the environment and the agricultural economy. In this study, the ARIMA model is used to predict and forecast rainfall and temperature in Chattogram, Bangladesh from 1953 to 2070 considering seasonal variations. Analyzed data indicated a substantial to a fairly significant upward trend in December, with a slight increase in rainfall between years 2021-2050 and 2050-2070. Rainfall reflects a more dominant rising trend in later parts of the selected four-time series, indicating more rainfall during the Monsoon season. Temperature follows an upward trend with time, the most significant positive trend occurring between 2021 and 2050, and a large negative trend occurring between 2050 and 2070. In the years 2021-2050, the yearly average temperature is expected to drop during the Rabi season. In April, May, July, and October, there is a significant negative connection between rainfall and temperature, meaning that temperatures will rise with less precipitation and vice versa.